Using weblogs to promote critical thinking through asychronous online discussion - Shahsavar, Zahra; Tan, Bee Hoon (The Asian Association of Teachers of English as a Foreign Language, 2010)
Findings from a few studies seem to indicate that weblogs have positive effects on learners by inducing them to think critically (Huffaker, 2008; Woo & Wang, 2009). In view of this recent interest, this paper aims to analyse the extent of bloggers and non-bloggers' critical thinking (CT) and how different weblogging strategies affect bloggers' CT. Forty four tertiary students participated in this study. The bloggers' posts and non-bloggers' written copies from the study were coded according to Newman, Webb, and Cochrane's (1996) CT model. In order to compare bloggers' writing reflections, four strategies were applied as follows: (a) blogging within a group with no feedback or extra influence, (b) blogging within a group with groupmates' comments, (c) sharing ideas with groupmates in the Sharing Corner at the weblog space before blogging individually in their own group, and (d) blogging to reflect on the groupmates' comments received. The results indicated that in promoting CT, blogging is seen to be more effective than traditional writing particularly if bloggers receive their group members' comments.